Determining Marketing Strategies for LRB Restaurant in Braga, Bandung - Sultan Meurizki Prasetyo; Gallang Perdhana Dalimunthe (PT. Publikasiku Academic Solution, 2026)
This study is motivated by the increasing competition in the food and beverage (F&B) industry, particularly in heritage tourism areas such as Braga, Bandung, where restaurants face challenges in sustaining revenue growth and brand visibility. The objective of this research is to analyze the current marketing mix of LRB Restaurant, identify internal and external business factors influencing its performance, and formulate an improved marketing strategy based on integrated strategic frameworks. The research employs a qualitative case study approach with 25 purposively selected participants consisting of staff, customers, and non-customers. Data were collected through semi-structured interviews and open-ended questionnaires, and analyzed using thematic analysis supported by NVivo software. The study integrates the Resource-Based View (RBV) with VRIO analysis, Porter's Five Forces, SWOT, TOWS, and the 7P Marketing Mix to develop a comprehensive strategic formulation. The findings reveal that LRB Restaurant possesses a strong strategic advantage in its location and ambience but suffers from weaknesses in digital marketing capability, brand awareness, and operational consistency during peak hours. External analysis shows high industry rivalry and very high customer bargaining power, requiring stronger differentiation strategies. The study concludes that an experience-based differentiation strategy combined with strengthened digital marketing and structured service operations is essential to improve the competitiveness and market positioning of LRB Restaurant.